ECOLOGICAL CONTENT ANALYSIS IN BOHLKE’S SKILLFUL READING AND WRITING - Pranoto, Yohanes Heri; Levinli, Vewent Fest (UC Journal: ELT, Linguistics and Literature Journal, 2022)
Ecology has long been a part of processes in current education. Hence it has become gentle evidence that the instillation of ecological values has been carried out extensively and thoroughly to students. One of the ecological promotion media is textbooks. This study aimed to analyze the ecological content of reading materials and instructions in the Skillful Reading and Writing book – a compulsory student book in the Critical Reading and Writing I course. Reading materials and instructions were on the analysis from the aspects developed by Rule and Atkinson (1994) namely appreciation of nature, realistic ecological problems, positive tone, appropriate illustrations, and hope for a solution. This study belongs to qualitative descriptive research with document study data collection techniques. The content analysis results revealed - at least - half of all readings in the book treat the natural environment. Of the five ecological aspects, they could be sorted according to the degree of conformity, namely positive tone (4.9), appreciation of nature (4.05), realistic ecological problems (4.15), appropriate illustrations (3.5), and hope for a solution (2.0). However, not all those selected readings are supplemented with learning instructions leading to real actions to preserve and appreciate environments. Therefore, teachers should make a purposively instructional adjustment to students’ conservation practices.